Ferromagnetic nanoparticles synthesis and functionalization for laccase enzyme immobilization - Rashid, Shah Samiur; Hasnat, Mustafa Abu; Mohd Hasbi, Ab. Rahim (Elsevier Ltd, 2021)
Ferromagnetic nanomaterials can easily be separated from the reaction media by using external magnetic force. Nanoparticles are excellent supporting materials that provide large surface area with high mass transfer rate. Ferromagnetic nanoparticle considered as an ideal immobilization supporting materials of biocatalysts for easy and fast recovery. In this study, ferromagnetic iron oxide nanoparticles were synthesized and functionalized as immobilization support materials. Amino functionalization of nanoparticles was performed to improve thermal stability and enzymatic activity. XRD planes at 2θ confirmed the successful synthesis of ferromagnetic nanoparticles. FTIR spectrum used to identify amino functionalization of nanoparticles, and size and surface morphology were studied through transmission electron microscopy (TEM).